"Legal Implications of Limiting Restorative Justice in Traffic Accidents Resulting in Death According to Article 235 of Law Number 22 of 2009 Concerning Road Traffic and Transportation" - Sukma W, Gesit (Jurnal Hukum Khaira Ummah, 2025)
Law Number 22 of 2009 concerning Road Traffic and Transportation (UU LLAJ), particularly Article 235, explicitly stipulates that traffic accidents resulting in death cannot be resolved through a restorative justice mechanism. This provision creates a juridical dilemma, especially when contrasted with the growing paradigm of restorative justice increasingly accommodated in the Indonesian criminal justice system, such as in the Regulation of the Chief of the Indonesian National Police Number 8 of 2021 on the Handling of Criminal Acts Based on Restorative Justice. This study aims to examine the juridical implications of such restrictions and assess their conformity with the principles of substantive justice, legal certainty, and the protection of the rights of both victims and offenders. The research method employed is normative legal research using a statute approach and a conceptual approach, complemented by empirical study through interviews with law enforcement officials and related stakeholders. The findings indicate that the prohibition of restorative justice in traffic accident cases resulting in death creates tension between legal certainty and the sense of justice within society, particularly when reconciliation occurs between the victim’s family and the offender. Although intended to uphold formal justice and provide victim protection, the restriction may in practice hinder case resolution that is more oriented toward substantive justice, humanity, and the restoration of social relations. Therefore, regulatory evaluation and harmonization are required to achieve a balance between legal certainty and the implementation of restorative justice in fatal traffic accident cases.